Method for improving ripple reduction during phase shedding in multiphase buck converters for SCADA systems - Mini P. Varghese; A. Manjunatha; T. V. Snehaprabha (Institute of Advanced Engineering and Science, 2021)
In the current digital environment, central processing unit (CPUs), field programmable gate array (FPGAs), application-specific integrated circuit (ASICs), as well as peripherals, are growing progressively complex. On motherboards in many areas of computing, from laptops and tablets to servers and Ethernet switches, multiphase phase buck regulators are seen to be more common nowadays, because of the higher power requirements. This study describes a four-stage buck converter with a phase shedding scheme that can be used to power processors in programmable logic controller (PLCs). The proposed power supply is designed to generate a regulated voltage with minimal ripple. Because of the suggested phase shedding method, this power supply also offers better light load efficiency. For this objective, a multiphase system with phase shedding is modeled in MATLAB SIMULINK, and the findings are validated.